2020
DOI: 10.1177/2331216520939776
|View full text |Cite
|
Sign up to set email alerts
|

No Influence of Musicianship on the Effect of Contralateral Stimulation on Frequency Selectivity

Abstract: The efferent system may control the gain of the cochlea and thereby influence frequency selectivity. This effect can be assessed using contralateral stimulation (CS) applied to the ear opposite to that used to assess frequency selectivity. The effect of CS may be stronger for musicians than for nonmusicians. To assess whether this was the case, psychophysical tuning curves (PTCs) were compared for 12 musicians and 12 nonmusicians. The PTCs were measured with and without a 60-dB sound pressure level (SPL) pink-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…Analyzing the studies presented in this review, it is important to point out that most studies have observed a greater magnitude of efferent effect, both ipsi- and contralaterally, in musical subjects when compared to a matched group of non-musicians. Only two studies are reported in which a favorable and significant difference in favor of musicians is not observed [ 51 , 52 ]. In the first case, it is highlighted that the musicians and the non-musicians group were not properly differentiated according to their musical experience, but it was according to a self-report and the application of the PROMS shortened test that this could have influenced the results as there was musical heterogeneity in the groups (musicians within the NM group and non-musicians within the M group).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyzing the studies presented in this review, it is important to point out that most studies have observed a greater magnitude of efferent effect, both ipsi- and contralaterally, in musical subjects when compared to a matched group of non-musicians. Only two studies are reported in which a favorable and significant difference in favor of musicians is not observed [ 51 , 52 ]. In the first case, it is highlighted that the musicians and the non-musicians group were not properly differentiated according to their musical experience, but it was according to a self-report and the application of the PROMS shortened test that this could have influenced the results as there was musical heterogeneity in the groups (musicians within the NM group and non-musicians within the M group).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, only a small number of studies have used this approach to investigate the efferent effect, and, furthermore, there is only one study that used this approach within the purview of this review. Tarnowska et al, 2020 [ 51 ] measured the effect of MOCR on physiological tuning curves (PTCs). Using simultaneous masking, the PTCs were measured and compared between 12 musicians and 12 non-musicians, at 2 kHz and 4 kHz frequencies, with and without contralateral pink noise stimulation at 60 dB SPL.…”
Section: Efferent Effect On Musiciansmentioning
confidence: 99%